Beijing red - Ryan, Alex (New York : Crooked Lane, 2016)
"When ex-Navy SEAL Nick Foley travels to China to find prupose and escape the demons of his past, he instead stumbles into a conspiracy his Special Forces training never prepared him for. A mysterious and deadly outbreak ravages a remote area of western China, and Nick finds himself the lead suspect in a bio-terrorism investigation being conducted by China's elite Snow Leopard counter-terrorism unit. To clear his name and avoid prosecution, he must team up with beautiful Chinese CDC microbiologist Dr. Dazhong "Dash" Chen to find who is really behind the attack. As their investigation proceeds, their budding friendship is tested by nationalistic loyalties and suspicion. In a race against time, Nick and Dash must risk everything to stop a mad man before he unleashes the world's next super-weapon in Beijing."--Dust jacked front flap.
Keywords: Suspense fiction; Mystery fiction